Dependence structure between TOURISM and TRANS sector indices of the stock exchange of Thailand - O. Puarattanaarunkorn (2018)
© 2014 by the Mathematical Association of Thailand. All rights reserved. Sriboonchitta et al. [1] argued that the traditional multivariate analysis imposed some strong assumptions and suggested to use the copula approach that provided better flexibility for the analysis. Thus, this study used the copula based ARMA-GARCH to examine the dependence structure between the price of two sectors, the Tourism & Leisure Index (TOURISM) and the Transportation & Logistics Index (TRANS), of the stock exchange of Thailand (SET). Our results provide evidence of a relatively small positive dependence between two sector indices. The BB1 copula that can capture both the lower tail and upper tail dependences is chosen to describe the dependence structure. The result shows that the lower tail dependence is stronger than the upper tail dependence. This information is useful for investors in recognizing that the chances for two indices will have to face the probability of joint occurrences of crashing all together.